Peningkatan Pemahaman tentang Pentingnya Program Keluarga Berencana di Dusun Mojosari Kelurahan Wonolelo Kecamatan Pleret Bantul - Totok Sundoro; Nida Tsaqila; Faris Ulin Nuha (Jurnal Abdimas Kesehatan (JAK), 2023)
The family planning program is currently only directed toward women. Thus causing the impression that it is women who have the responsibility in terms of regulating pregnancy. Men's participation as well as the head of the family plays an important role in family planning programs in several countries, including Indonesia. This community service program aims to encourage husbands' participation in family planning programs by improving understanding of contraceptive methods KB MOP (Male Method of Operation). Participants in this activity were residents of Dusun Mojosari Wonolelo, Bantul, targeting husbands or heads of families. The method used is Urgency, Seriousness, and Growth (USG). Community service is carried out by educating the use of several types of contraceptive methods/methods as well as myths and facts, especially KB MOP. Then he carried out educational innovations about family planning through simulations from videos. This activity was carried out for approximately 3 hours. After participating in this activity, it is hoped that men, especially husbands, will have extensive knowledge about contraceptive methods. This community service is carried out in an integrated manner through Field Learning Practices for STIKes Surya Global Yogyakarta Students. Forms of information and education about myths and facts about contraceptive methods and family planning are the approaches taken in this activity. Through this community service program it has been proven to be able to increase men's knowledge on family planning issues. The program target participates actively during the activity, so that their knowledge of family planning increases through community involvement starting from the process of prioritizing problems so that the interventions carried out really represent the needs of the community.